2021
DOI: 10.1039/d0ma00851f
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase CO2 electroreduction over Sn–Cu hollow fibers

Abstract: CO2 electroreduction to value-added chemicals by virtue of renewable electricity is significant for carbon emission abatement and renewable energy converting/storage. Conventional CO2 electroreduction occurred in aqueous solution or ionic liquid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Figure 2 showed that all catalysts had the capability to produce methanol (CH 3 OH) and multicarbon products mainly including acetaldehyde (CH 3 CHO), propanal (CH 3 CH 2 CHO) and acetone (CH 3 COCH 3 ), while ethanol (CH 3 CH 2 OH) was also formed on Cu foam. Note that no hydrogen was produced over all catalysts, indicating the merit of gas-phase CO 2 electroreduction, i.e., the complete suppression of hydrogen evolution reaction (HER), as previously reported [25]. Furthermore, acetaldehyde was the most favorable product over all catalysts, and the faradaic efficiency (FE) of acetaldehyde over Cu 2 O NWs were much higher than those over Cu foam and CuO NWs.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Figure 2 showed that all catalysts had the capability to produce methanol (CH 3 OH) and multicarbon products mainly including acetaldehyde (CH 3 CHO), propanal (CH 3 CH 2 CHO) and acetone (CH 3 COCH 3 ), while ethanol (CH 3 CH 2 OH) was also formed on Cu foam. Note that no hydrogen was produced over all catalysts, indicating the merit of gas-phase CO 2 electroreduction, i.e., the complete suppression of hydrogen evolution reaction (HER), as previously reported [25]. Furthermore, acetaldehyde was the most favorable product over all catalysts, and the faradaic efficiency (FE) of acetaldehyde over Cu 2 O NWs were much higher than those over Cu foam and CuO NWs.…”
Section: Resultssupporting
confidence: 74%
“…While gas-phase CO2 electroreduction highly depended o the conductivity of proton exchange membrane, resulting in the low current densitie [26]. In addition, the total FE of the products over Cu foam and CuO NWs were found t be less than 100% over the entire potential range because of high charge transfe resistance and diffusion resistance in gas-solid interface reaction system [25,27,28 Therefore, Cu2O NWs and Cu foam exhibited the preferable activities of gas-phase CO electroreduction to multicarbon oxygenates compared to CuO NWs. The intrinsic active composition and C-C coupling mechanism of Cu-based catalysts were further investigated by operando Raman and DRIFTS, and the illustration of operando system were shown in Figure S6.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the appealing considerations, unsatisfactory overall efficiencies and poor stability are generally being reported for GPCEC and only limited progress was made in terms of material performances, for example, by using bimetallic Cu-based systems and special cell configurations. 8 It is generally recognised that understanding the mechanism of the electrocatalyst activation and deactivation at the molecular level can guide the design of improved electrodes. Operando spectroscopy serves this purpose well as demonstrated by the many contributions published in recent years on the electrocatalytic conversion of CO 2 in liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, stainless steel mesh (SSM) is covered on the surface of ion exchange membrane, serving as the anode. [ 395 ] The current study is mainly focused on the first and second generation owing to a considerable ion/electron transfer and the appreciable current density, while the all‐solid system is limited by a relatively poor current density, which remains to be further optimized from the aspect of solid‐electrolyte optimization and device assembly.…”
Section: Optimizing Strategiesmentioning
confidence: 99%